Expert Opinions and Consensus Recommendations for the Evaluation and Management of Insomnia in Clinical Practice: Joint Statements of Five Italian Scientific Societies - Palagini, Laura; Manni, Raffaele; Aguglia, Eugenio; Amore, Mario; Brugnoli, Roberto; Girardi, Paolo; Grassi, Luigi; Mencacci, Claudio; Plazzi, Giuseppe; Minervino, Antonino; Nobili, Lino; Biggio, Giovanni (Frontiers in Psychiatry, 2020)
Background: Insomnia is the most commonly reported sleep problem in industrialized countries worldwide being present in about 36.8% of the general population. In Italy such a percentage seems to be even higher. Although insomnia can be an independent disorder, it is most frequently observed as a comorbid condition and may precipitate, exacerbate, or prolong a broad range of comorbid conditions including physical and mental illnesses. Evaluating and targeting insomnia in the Italian clinical practice should be a priority. Methods: The present expert options and recommendations development process was based on the RAND/UCLA Appropriateness Method for conceptualizing, designing, and carrying out the appropriateness of procedures for the diagnosis and treatment. Only available options in Italy were taken into considerations. Results: We evaluated 12 international guidelines and 12 most recent systematic reviews for insomnia evaluation and treatment produced in the last 10 years. Conclusions: Our findings suggested that symptoms of insomnia must always be assessed in the Italian clinical practice by evaluating nocturnal and daytime symptoms, comorbid conditions and lifestyle. In a patient with chronic insomnia with and without comorbidity insomnia treatment should be always initiated. CBT-Insomnia therapy should be the first option accordingly to availability. The choice of the drug should be based on different factors such as type of insomnia, age, comorbidities, potential side effects. Melatonin 2 mg prolonged release should be the first choice in subjects >55 years. If the choice would be a Z-drug or a short-acting benzodiazepine (in subjects <65 years old) or a sedating antidepressant, the use should be in the short term (<4 weeks) and then proceeds to tapering under clinical monitoring